Suggestopedia Method Application Based on Sasando Instrumental Music in Optimizing Reading Comprehension Skills - Pali, Agustina; Rando, Agnes Remi (Universitas Pendidikan Ganesha, 2020)
The success of the English learning process is largely determined by the students' reading comprehension ability. However, not all teachers can apply appropriate learning methods so that innovations are needed in learning. This study aims to describe the extent to which the improvement of students' reading comprehension competencies through the application of the suggestopedia method is based on Sasando instrumental music. This type of research is classroom action research in the form of collaboration between researchers and English teachers. The sample in this study were students of class VA with a total of 27 students. Data were collected through pre-test, post-test, and observation. The results showed that there was an increase in the value of 72.22% from the pre-test cycle 1 and then an increase to 83.81% from cycle 1 to cycle 2. So, it can be concluded that the suggestopedia method based on Sasando instrumental music can be a method that is effective for teaching reading comprehension to fifth grade.